Factors Influencing the Use of Speech Style in Steve Harvey’s Talk Show Videos - Prastowo, FR Suluh Adiguna; Fiani, Ani; Syafitri, Dewi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research analyzed the factors influenced the speech style used in Steve Harvey’s talk show videos. The objectives of this research were to describe the factors influenced the speech style based on Holmes’s theory occurred in Steve Harvey’s talk show videos. The method of the research was a descriptive qualitative. The technique for collecting the data was audio-visuals. The researcher used videos talk show of Steve Harvey uploaded in January 2024 on Steve TV Show YouTube channel. There were 9 talk show videos uploaded on January 2024. In this research, the researcher found the factors influenced the speech style consist of setting, participants, topic, and function. In conclusion the factors influenced the speech styles used by Steve Harvey in his talk show the first is participants, in his talk show are families and teenagers, no participants from the political elite or someone who has a high position such as president or minister. The second is setting used by Steve Harvey in his talk show are studio talk show and via online or video call.The third is the topic, in Steve Harvey’s talk show during January 2024 is about life experiences and the last is function, the function is directive utterances or asking people to do something. Keywords: Factors Influenced Speech Styles, Sociolinguistics, Talk Show